THEORETICAL AND PRACTICAL ASPECTS OF THE POETICS OF HISTORICAL NOVELS CREATED DURING THE "SOUTHERN RENAISSANCE" IN LINGUISTIC CONTEXT - Razzakov Bakhrom Abdugafurovich (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This paper explores the theoretical and practical aspects of the poetics of historical novels produced during the "Southern Renaissance" within a linguistic context. The Southern Renaissance, a literary and cultural movement emerging in the Southern United States during the early to mid-20th century, saw a revival of interest in regional history, identity, and cultural memory. Focusing on the works of key Southern authors, the study investigates how the poetics of historical novels intersect with linguistic features, such as dialect, vernacular speech, and narrative structures, to construct historical consciousness and regional identity. Theoretical analysis will draw on key literary and linguistic theories related to historical fiction, regionalism, and the interplay between language and memory. In practical terms, the study will examine specific texts, considering how the manipulation of language both reflects and shapes the portrayal of Southern history, culture, and social dynamics. This paper aims to provide a deeper understanding of how historical novels in the Southern Renaissance not only narrate the past but also participate in the ongoing negotiation of linguistic and cultural identities in the context of the American South.